Preparation method and application of super-alkali-resistant bis-piperidinium cross-linked anion exchange membrane
By introducing binaphthalene units and flexible bispiperidinium crosslinking agent into the anion exchange membrane, the problem of poor alkali resistance in high pH environments is solved, and efficient ionic conductivity and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510086314.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing anion exchange membranes are chemically unstable and have poor alkali resistance in high pH environments, which limits their application in flow batteries, fuel cells and water electrolysis.
The ion conduction and chemical stability are improved by introducing large volume bispiperidinium units and flexible bispiperidinium cross-linking agent based on chemical stability.
It has achieved excellent ionic conductivity, strong alkalinity stability and electrochemical properties of the anion exchange membrane, and has potential application prospects.
Smart Images

Figure CN119875044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anion exchange membranes, and in particular relates to a preparation method and application of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane. Background Art
[0002] Anion exchange membranes have great potential in addressing the shortage of non-renewable energy and global warming, and are gaining increasing attention as energy conversion and storage devices. However, relative to the commercial benchmark Nafion proton exchange membrane, most existing anion exchange membranes exhibit unsatisfactory alkaline resistance due to chemically unstable cationic groups and polymer backbones in high pH environments, which significantly limits their practical applications.
[0003] In recent years, advanced anion exchange membrane materials with ether-free polymer backbones have attracted extensive attention as a promising alternative to conventional anion exchange membrane materials with ether-containing backbones, due to their remarkable chemical durability due to the absence of alkalinity-sensitive ether bonds. During the boom of ether-free polymers, poly(arylene) polymer backbones prepared by acid-catalyzed polycondensation gained popularity due to their extraordinary durability and simple synthetic procedures. However, these materials still have several disadvantages that limit their large-scale commercialization. Anion exchange membranes based on quaternized poly(arylene piperidines) with excessive ion content, especially quaternized poly(biphenyl piperidines), usually exhibit severe dimensional expansion, compromising their mechanical properties and durability. The introduction of bulky rigid aromatic structures into the polymer backbone can prevent chain stacking and increase the internal free volume to develop ion transport capacity. However, the bulky aromatic groups tend to increase the hardness and brittleness of the membranes, resulting in unsatisfactory mechanical properties.
[0004] Cross-linking provides an effective way to promote the performance development of anion exchange membranes. However, conventional cross-linkers composed of hydrophobic structures are usually constructed for the ionic conductivity of anion exchange membranes. Many researchers have conducted extensive research on the optimal structure of cross-linkers to improve the physicochemical durability of anion exchange membranes and accelerate anion conduction. The piperidinium cationic group is remarkably stable under harsh alkaline conditions, which is due to the low ring strain and effective steric protection provided by the symmetrical six-membered ring structure. However, there are significant differences in the alkali resistance of piperidinium cations with different substituents. So far, few publications have been published on the effects of various cross-linkers containing piperidinium cationic groups on membrane properties. Therefore, enriching and optimizing piperidinium cross-linkers through molecular structure design is a top priority for advanced anion exchange membrane materials.
[0005] The present invention aims at the problems faced by current anion exchange membranes for flow batteries, fuel cells and water electrolysis, and proposes a cross-linked anion exchange membrane, which is a bipiperidinium cross-linked anion exchange membrane based on a chemically stable ether-free poly (binaphthyl co-terphenyl piperidine) main chain. The bulky binaphthyl units introduced into the polymer main chain can improve ion conduction by expanding the free volume inside the anion exchange membrane. In addition, adding a flexible bipiperidinium cross-linking agent into the ether-free main chain can enhance ion conductivity and chemical stability by establishing different microphase separations and constructing sufficient ion conduction channels. The prepared anion exchange membrane has excellent ion conductivity, strong alkaline stability and excellent electrochemical performance, and has potential application prospects. Summary of the invention
[0006] In order to solve the above problems, the present invention discloses a preparation method and application of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] The present invention provides a super alkali-resistant bispiperidinium cross-linked anion exchange membrane, and the structure of the super alkali-resistant bispiperidinium cross-linked anion exchange membrane is shown in Formula 1:
[0009]
[0010] In Formula 1, A1 is independently selected from one or more of benzene, biphenyl, m-terphenyl, p-terphenyl, binaphthyl, o-quaterphenyl, m-quaterphenyl, and p-quaterphenyl;
[0011] The structure of the R1 part is shown in formula 2:
[0012]
[0013] In Formula 2, R2 is independently selected from any one of hydrogen, methyl, ethyl, propyl, butyl, phenyl, and substituted phenyl;
[0014] x is any value between 8 and 15.
[0015] The present invention also provides a method for preparing a super alkali-resistant bispiperidinium cross-linked anion exchange membrane, comprising the following steps:
[0016] Synthesis of S01 bispiperidinium crosslinker: dissolve piperidine monomer in an organic solvent at 50-90°C, mix with inorganic salt and stir for 0.1-3h, then add halogenated hydrocarbon, continue stirring for 1-5 days and filter to remove inorganic salt in the mixed solution, pour the filtered solution into a certain amount of deionized water, and then add organic solvent for extraction; dry the organic layer with inorganic salt desiccant, evaporate the solvent in the solution with a rotary evaporator to obtain a bispiperidinium crosslinker;
[0017] S02 polymer synthesis and cross-linking reaction: the aromatic compound and the carbonyl compound are mixed and dissolved in an organic solvent, and polymerized under the catalysis of an acid, and then the bispiperidinium cross-linking agent in step (1) is added, and then an inorganic salt and an organic solvent are added, and stirred at 50 to 90° C. for 1 to 5 days, and after cooling, a certain concentration of alkali solution is added and stirred for 0.5 to 3 days, and the obtained polymer is added to ethyl acrylate to precipitate it, and the obtained powder is purified and impurities are removed with deionized water, and dried to obtain a bispiperidinium cross-linked polymer;
[0018] Preparation of S03 cross-linked anion exchange membrane: dissolve the bispiperidinium cross-linked polymer obtained in step (2) in an organic solvent, filter the solution and cast it on a glass plate, dry it in an oven at 70-100°C for 12-36 hours to form a membrane, remove the membrane and soak it in alkaline solution for 24-72 hours for ion exchange, and then soak it in degassed pure water to obtain a super alkali-resistant bispiperidinium cross-linked anion exchange membrane.
[0019] Furthermore, in step S01, the organic solvent is one or more of ethanol, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the piperidine monomer is one or more of piperidine, 2-methylpiperidine, 3-methylpiperidine, 3,5-dimethylpiperidine, 4-methylpiperidine, and 4-phenylpiperidine; the inorganic salt is one of potassium carbonate and sodium carbonate; the halogenated hydrocarbon is one of 1,6-dibromohexane, 1,5-dibromopentane, and 1,4-dibromobutane; and the inorganic salt desiccant is one of anhydrous calcium chloride and anhydrous magnesium sulfate.
[0020] Furthermore, in step S01, the molar ratio of the piperidine monomer to the inorganic salt to the halogenated hydrocarbon is 1:1 to 1:3.
[0021] Further, in step S02, the aromatic compound is one or more of benzene, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, quaterphenyl, o-quaterphenyl, m-quaterphenyl, p-quaterphenyl, o-meta-quaterphenyl, p-meta-quaterphenyl, and binaphthyl; the carbonyl compound is one of 1-methyl-4-piperidone, 1,2-dimethyl-4-piperidone, 1,3,5-trimethyl-4-piperidone, and 1,2,6-trimethyl-4-piperidone; and the molar ratio of the aromatic compound to the carbonyl compound is 1:1 to 1:2.
[0022] Furthermore, in step S02, the acid is one or more of trifluoromethanesulfonic acid, trifluoroacetic acid, pentafluoroethanesulfonic acid, perfluoropropionic acid, and heptafluorobutyric acid; and the molar ratio of the aromatic compound to the acid is 1:8 to 1:20.
[0023] Furthermore, in step S02, the base is one of sodium hydroxide and potassium hydroxide; the concentration of the alkali solution is 0.1-50 mol / L; the molar ratio of the aromatic compound, the carbonyl compound, the bispiperidinium cross-linking agent, the inorganic salt, and the organic solvent is 20:22:1.2:6:1-20:22:1.2:12:2; the polymerization temperature under acid catalysis is -5-5°C, and the time is 5-10h.
[0024] Furthermore, in step S03, the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the mass ratio of the bispiperidinium cross-linked polymer to the organic solvent is 1:30 to 1:100; the alkali solution is one of sodium hydroxide and potassium hydroxide; and the concentration of the alkali solution is 0.1 to 50 mol / L.
[0025] The present invention also provides an application of a cross-linked anion exchange membrane prepared by the preparation method as described above in a liquid flow battery, wherein the liquid flow battery includes an all-vanadium liquid flow battery, an organic liquid flow battery, an iron-chromium liquid flow battery, a zinc-bromine liquid flow battery, and an organic-inorganic composite liquid flow battery.
[0026] The present invention also provides an application of a cross-linked anion exchange membrane prepared by the preparation method described above in a fuel cell, wherein the fuel cell is an alkaline fuel cell.
[0027] The present invention also provides an application of the cross-linked anion exchange membrane prepared by the preparation method described above in water electrolysis, wherein the water electrolysis is alkaline water electrolysis.
[0028] The beneficial effects of the present invention are:
[0029] The super alkali-resistant bispiperidinium cross-linked anion exchange membrane prepared by the preparation method of the present invention has a bulky binaphthyl unit introduced into the polymer main chain, which increases the free volume inside the anion exchange membrane, thereby improving the ion conductivity. The flexible bispiperidinium cross-linking agent is introduced into the main chain to establish obvious microphase separation and construct sufficient ion conduction channels, thereby enhancing the ion conductivity and chemical stability. The super alkali-resistant bispiperidinium cross-linked anion exchange membrane prepared by the present invention has excellent ion conductivity, strong alkaline stability and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1H NMR spectrum of the cross-linked anion exchange membrane of Example 1 of the present invention;
[0031] Figure 2 1HNMR spectrum of the cross-linked anion exchange membrane of Example 2 of the present invention;
[0032] Figure 3 1HNMR spectrum of the cross-linked anion exchange membrane of Example 3 of the present invention;
[0033] Figure 4 1HNMR spectrum of the cross-linked anion exchange membrane of the comparative example of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0035] Example 1
[0036] (1) Synthesis of crosslinking agent: 0.99 g of 4-methylpiperidine was dissolved in 50 mL of acetonitrile at 70° C., mixed with 0.3 g of potassium carbonate and stirred for 2 h, then 4.98 g of 1,6-dibromohexane was added, stirred for 48 h, the heating temperature was adjusted to 60° C., stirred for 24 h, and filtered, the filtered solution was poured into 250 mL of deionized water, and then 30 mL of 1,6-dibromohexane was added for extraction. The organic layer was dried with anhydrous calcium chloride desiccant, and the solvent in the solution was evaporated using a rotary evaporator to obtain a bispiperidinium crosslinking agent.
[0037] (2) Polymer synthesis and cross-linking reaction: 2.54 g of binaphthyl, 2.3 g of terphenyl and 1.24 g of 1-methyl-4-piperidone were mixed and dissolved in 100 mL of dichloromethane, and 1 g of trifluoromethanesulfonic acid and 0.5 g of trifluoroacetic acid were added. After stirring for 1 h, 0.5 g of the bispiperidinium cross-linking agent in step (1), 1.3 g of potassium carbonate and 60 mL of dimethyl sulfoxide were added. The mixture was stirred at 80° C. for 2 days. After the solution was cooled to 30° C., 200 mL of 1 mol / L sodium hydroxide solution was added. The stirring was continued for 1 day. The obtained mixed solution was added into 1 L of ethyl acrylate to precipitate the polymer. The obtained powder was purified and impurities were removed with deionized water. After drying, a cross-linked polymer was obtained.
[0038] (3) Preparation of anion exchange membrane: Take 1 g of the cross-linked polymer obtained in step (2) and dissolve it in 50 mL of DMSO. After the solution is filtered, cast it on a 5 cm × 5 cm glass plate and dry it in an oven at 80°C for 24 h. After removing the membrane, immerse it in 1 mol / L NaOH for ion exchange for 48 h, and then remove it and immerse it in degassed pure water to obtain a cross-linked anion exchange membrane.
[0039] Example 2
[0040] (1) Synthesis of cross-linking agent: 0.85 g of piperidine was dissolved in 50 mL of acetonitrile at 70° C., mixed with 0.3 g of potassium carbonate and stirred for 2 h, then 4.98 g of 1,6-dibromohexane was added, stirred for 48 h, the heating temperature was adjusted to 60° C., stirred for 24 h, and filtered, the filtered solution was poured into 250 mL of deionized water, and then 30 mL of 1,6-dibromohexane was added for extraction. The organic layer was dried with anhydrous calcium chloride desiccant, and the solvent in the solution was evaporated using a rotary evaporator to obtain a bispiperidinium cross-linking agent.
[0041] (2) Polymer synthesis and cross-linking reaction: The preparation method is the same as that in Example 1 (2), to obtain a cross-linked polymer.
[0042] (3) Preparation of cross-linked anion exchange membrane: The preparation method is the same as that in Example 1 (3), to obtain a cross-linked anion exchange membrane.
[0043] Example 3
[0044] (1) Synthesis of crosslinking agent: 1.61 g of 4-phenylpiperidine was dissolved in 50 mL of acetonitrile at 70° C., mixed with 0.3 g of potassium carbonate and stirred for 2 h, then 4.98 g of 1,6-dibromohexane was added, stirred for 48 h, and then the heating temperature was adjusted to 60° C. After stirring for 24 h, the mixture was filtered, and the filtered solution was poured into 250 mL of deionized water, and then 30 mL of 1,6-dibromohexane was added for extraction. The organic layer was dried with anhydrous calcium chloride desiccant, and the solvent in the solution was evaporated using a rotary evaporator to obtain a bispiperidinium crosslinking agent.
[0045] (2) Polymer synthesis and cross-linking reaction: The preparation method is the same as that in Example 1 (2), to obtain a cross-linked polymer.
[0046] (3) Preparation of cross-linked anion exchange membrane: The preparation method is the same as that in Example 1 (3), to obtain a cross-linked anion exchange membrane.
[0047] Comparative Example
[0048] (1) Polymer synthesis and cross-linking reaction: 2.54 g of binaphthyl, 2.3 g of terphenyl and 1.24 g of 1-methyl-4-piperidone were mixed and dissolved in 100 mL of dichloromethane, and 1 g of trifluoromethanesulfonic acid and 0.5 g of trifluoroacetic acid were added. After stirring for 1 h, 0.25 mL of iodomethane, 1.3 g of potassium carbonate and 60 mL of dimethyl sulfoxide were added. The mixture was stirred at 80° C. for 2 days. After the solution was cooled to 30° C., 200 mL of 1 mol / L sodium hydroxide solution was added. The stirring was continued for 1 day. The obtained mixed solution was added to 1 L of ethyl acrylate to precipitate the polymer. The obtained powder was purified and impurities were removed with deionized water. After drying, a cross-linked polymer was obtained.
[0049] (2) Preparation of anion exchange membrane: Take 1 g of the polymer obtained in step (1) and dissolve it in 50 mL of DMSO. After the solution is filtered, cast it on a 5 cm × 5 cm glass plate and dry it in an oven at 80°C for 24 h. After removing the membrane, immerse it in 1 mol / L NaOH for ion exchange for 48 h, then remove it and immerse it in degassed pure water to obtain a cross-linked anion exchange membrane.
[0050] The NMR data of the anion exchange membranes prepared in Examples 1-3 and Comparative Examples are shown in the attached figure. Figure 1-4 shown.
[0051] From the peak position and peak area of 1HNMR spectrum, it can be seen that the polymer was successfully synthesized, which is in line with the expected results.
[0052] The partial performance comparison of the anion exchange membranes prepared in Examples 1-3 and the comparative example is shown in Table 1. The crosslinking degree is determined based on the integral ratio of aliphatic-H (1.1-1.8 ppm) to aromatic-H (7.2-7.9 ppm) in the 1H NMR spectrum, and the ion exchange capacity, water absorption, swelling ratio, tensile strength, elongation at break and toughness are obtained by testing according to the national standard GB / T 1040-92 method.
[0053] Table 1 Comparison of the performance of anion exchange membranes prepared in Examples 1-3 and Comparative Examples
[0054]
[0055] It can be seen from the mechanical properties comparison table 1 of the above anion exchange membrane that the anion exchange membrane disclosed in the embodiment of the present invention has a higher ion exchange capacity, and compared with the comparative example, the addition of the bispiperidinium crosslinking agent improves the ion exchange capacity of Examples 1-3 to varying degrees. The anion exchange membrane disclosed in the embodiment of the present invention also has a moderate water absorption rate and good swelling resistance. Compared with the comparative example, the introduction of the bispiperidinium crosslinking agent is more conducive to enhancing the water retention capacity of the membrane and the formation of a hydrophilic crosslinked network, so that the anion exchange membrane has better water absorption and lower swelling rate. Sufficient ion exchange capacity and good swelling resistance are the key to the long-term and efficient use of anion exchange membranes in batteries. It can also be seen from the table that, in Examples 1-3 and the comparative example at the same thickness, the addition of the bispiperidinium crosslinker has little effect on the tensile strength of the membrane, but can greatly improve the elongation at break and toughness of the membrane, proving that the addition of the bispiperidinium crosslinker as a flexible chain can soften the anion exchange membrane, effectively reduce the difficulty of battery assembly, reduce the depreciation rate of the anion exchange membrane, and extend the service life, which plays a vital role in the practical application of the anion exchange membrane.
[0056] The water contact angles in air of the anion exchange membranes prepared in Examples 1-3 and the comparative example are shown in Table 2. The electrical conductivity was measured according to the national standard GB / T 24368-2009.
[0057] Table 2 Water contact angles in air of anion exchange membranes prepared in Examples 1-3 and Comparative Examples
[0058] Example Example 1 Example 2 Example 3 Comparative Example Water contact angle in air / ° 61.1 67.0 74.7 83.1
[0059] It can be seen from the performance comparison table 2 of the anion exchange membranes mentioned above that the anion exchange membranes disclosed in the embodiments of the present invention are all hydrophilic membranes, wherein the addition of the bispiperidinium crosslinking agent is conducive to the formation of a hydrophilic network, and the hydrophilicity of embodiments 1-3 is stronger than that of the comparative example.
[0060] The conductivity of the anion exchange membranes prepared in Examples 1-3 and the comparative example at different temperatures is shown in Table 3. The conductivity is obtained by testing according to the national standard GB / T 42080-2023 method.
[0061] Table 3 Conductivity of anion exchange membranes prepared in Examples 1-3 and Comparative Examples at different temperatures
[0062]
[0063] It can be seen from Table 3 of the conductivity of the anion exchange membrane at different temperatures that the anion exchange membrane disclosed in the embodiment of the present invention has a high OH - The conductivity of OH in Examples 1-3 is - The conductivity is always higher than that of the comparative example. This is because the hydrophilic group introduced by the bispiperidinium crosslinker causes the ion exchange capacity and water absorption rate of Examples 1-3 to be higher than that of the comparative example (see Table 1). - The key to conductivity. Ion transport characteristics are one of the most critical parameters of anion exchange membranes, and have an important impact on power output performance and its application.
[0064] The anion exchange membranes prepared in Examples 1-3 and the comparative example were immersed in 2 mol / L NaOH at 80° C. for 65 days. The conductivity loss of the anion exchange membranes before and after the immersion is shown in Table 4.
[0065] Table 4 Conductivity loss of anion exchange membranes prepared in Examples 1-3 and Comparative Examples before and after immersion in NaOH solution
[0066] Example Example 1 Example 2 Example 3 Comparative Example Conductivity loss / % 4 3 6 7
[0067] It can be seen from the above table that the anion exchange membrane disclosed in the embodiment of the present invention has better alkali resistance than the comparative example, and the spatial shielding brought by the addition of the flexible bispiperidinium crosslinker can well increase the OH - The difficulty of attack, the anion exchange membrane with excellent alkaline stability can provide a strong guarantee for the long-term operation of the battery.
[0068] The anion exchange membranes prepared in Examples 1-3 and Comparative Examples were assembled as electrolyte membranes in an aqueous liquid flow battery. The positive electrode electrolyte active substance was TEMPO-ammonium chloride, the negative electrode electrolyte active substance was 1,1'-dimethyl-4,4'-bipyridinium dichloride hydrate, and the supporting electrolyte was sodium chloride. The above assembled liquid flow battery was subjected to a charge and discharge cycle test at 18-30°C, and the current density was 80 mA / cm 2 ,The test results are shown in Table 5. It can be seen that there is no obvious attenuation of the film within 50 cycles of charge and discharge.
[0069] Table 5 Performance test table of anion exchange membranes prepared in Examples 1-3 and Comparative Examples in flow batteries
[0070] Example Voltage efficiency / % Coulomb efficiency / % Energy efficiency / % Example 1 88.29 99.06 88.05 Example 2 83.54 98.69 83.23 Example 3 84.36 98.65 83.64 Comparative Example 80.02 98.20 79.99
[0071] It can be seen from the above table that the aqueous liquid flow battery assembled with the anion exchange membrane material disclosed in the embodiments of the present invention exhibits good battery performance. Based on the effect of the addition of the bispiperidinium crosslinker on conductivity, the battery performance of Examples 1-3 is greatly improved compared to the comparative example.
[0072] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A super alkali-resistant bispiperidinium cross-linked anion exchange membrane, characterized in that: The structure of the super alkali-resistant bispiperidinium cross-linked anion exchange membrane is shown in Formula 1: In Formula 1, A1 is independently selected from one or more of benzene, biphenyl, m-terphenyl, p-terphenyl, binaphthyl, o-quaterphenyl, m-quaterphenyl, and p-quaterphenyl; The structure of R1 is shown in Formula 2: In Formula 2, R2 is independently selected from any one of hydrogen, methyl, ethyl, propyl, butyl, phenyl, and substituted phenyl; x is any value between 8 and 15.
2. A method for preparing the super alkali-resistant bispiperidinium cross-linked anion exchange membrane as claimed in claim 1, characterized in that: The following steps are involved: Synthesis of S01 bispiperidinium crosslinker: dissolve piperidine monomer in an organic solvent at 50-90°C, mix with inorganic salt and stir for 0.1-3h, then add halogenated hydrocarbon, continue stirring for 1-5 days and filter to remove inorganic salt in the mixed solution, pour the filtered solution into a certain amount of deionized water, and then add organic solvent for extraction; dry the organic layer with inorganic salt desiccant, evaporate the solvent in the solution with a rotary evaporator to obtain a bispiperidinium crosslinker; S02 polymer synthesis and cross-linking reaction: the aromatic compound and the carbonyl compound are mixed and dissolved in an organic solvent, and polymerization is carried out under the catalysis of an acid, and then the bispiperidinium cross-linking agent in step (1) is added, and then an inorganic salt and an organic solvent are added, and the mixture is stirred at 50-90°C for 1-5 days. After cooling, an alkali solution is added and the stirring is continued for 0.5-3 days. The obtained polymer is added to ethyl acrylate to precipitate it, and the obtained powder is purified and impurities are removed with deionized water, and the bispiperidinium cross-linked polymer is obtained after drying. S03 preparation of a cross-linked anion exchange membrane: the bispiperidinium cross-linked polymer obtained in step (2) is dissolved in an organic solvent, and after dissolution and filtration, it is cast on a glass plate, and dried in an oven at 70-100°C for 12-36 hours to form a membrane. After the membrane is removed, it is immersed in an alkali solution for 24-72 hours for ion exchange, and then immersed in degassed pure water to obtain a super alkali-resistant bispiperidinium cross-linked anion exchange membrane.
3. The method for preparing a super alkali-resistant bispiperidinium cross-linked anion exchange membrane according to claim 2, characterized in that: In step S01, the organic solvent is one or more of ethanol, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the piperidine monomer is one or more of piperidine, 2-methylpiperidine, 3-methylpiperidine, 3,5-dimethylpiperidine, 4-methylpiperidine, and 4-phenylpiperidine; the inorganic salt is one of potassium carbonate and sodium carbonate; the halogenated hydrocarbon is one of 1,6-dibromohexane, 1,5-dibromopentane, and 1,4-dibromobutane; the inorganic salt desiccant is one of anhydrous calcium chloride and anhydrous magnesium sulfate; and the molar ratio of the piperidine monomer to the inorganic salt to the halogenated hydrocarbon is 1:1 to 1:
3.
4. The method for preparing a super alkali-resistant bispiperidinium cross-linked anion exchange membrane according to claim 2, characterized in that: In step S02, the aromatic compound is one or more of benzene, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, quaterphenyl, o-quaterphenyl, m-quaterphenyl, p-quaterphenyl, o-meta-quaterphenyl, p-meta-quaterphenyl, and binaphthyl; the carbonyl compound is 1-methyl-4-piperidone, 1,2-dimethyl-4-piperidone, 1,3,5-trimethyl-4-piperidone, 1,2,6- One of trimethyl-4-piperidone; the molar ratio of the aromatic compound to the carbonyl compound is 1:1 to 1:
2.
5. The method for preparing a super alkali-resistant bispiperidinium cross-linked anion exchange membrane according to claim 2, characterized in that: In step S02, the acid is one or more of trifluoromethanesulfonic acid, trifluoroacetic acid, pentafluoroethanesulfonic acid, perfluoropropionic acid, and heptafluorobutyric acid; and the molar ratio of the aromatic compound to the acid is 1:8 to 1:
20.
6. The method for preparing a super alkali-resistant bispiperidinium cross-linked anion exchange membrane according to claim 2, characterized in that: In step S02, the alkali is one of sodium hydroxide and potassium hydroxide; the concentration of the alkali solution is 0.1-50 mol / L; The molar ratio of the aromatic compound, the carbonyl compound, the bispiperidinium crosslinking agent, the inorganic salt and the organic solvent is 20:22: 1.2:6:1~20:22:1.2:12:2; the polymerization temperature under acid catalysis is -5~5℃, and the time is 5~10h.
7. The preparation method and application of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane as claimed in claim 2, characterized in that: In step S03, the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and the mass ratio of the bispiperidinium cross-linked polymer to the organic solvent is 1: 30~1:100; the alkali solution is one of sodium hydroxide and potassium hydroxide; the concentration of the alkali solution is 0.1~50mol / L.
8. An application of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane prepared by the preparation method according to any one of claims 2 to 7 in a liquid flow battery, characterized in that: The flow battery includes an all-vanadium flow battery, an organic flow battery, an iron-chromium flow battery, a zinc-bromine flow battery, and an organic-inorganic composite flow battery.
9. Use of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane prepared by the preparation method according to any one of claims 2 to 7 in a fuel cell, characterized in that: The fuel cell is an alkaline fuel cell.
10. Use of a super alkali-resistant bispiperidinium cross-linked anion exchange membrane prepared by the preparation method according to any one of claims 2 to 7 in water electrolysis, characterized in that: The water electrolysis is alkaline water electrolysis.